Crystalloid or colloid for goal-directed fluid therapy in colorectal surgery - Yates, D.R.A.; Davies, S.J.; Milner, H.E.; Wilson, R.J.T. (British journal of anaesthesia : BJA, 2014)
Goal-directed fluid therapy has been shown to improve outcomes after colorectal surgery, but the optimal type of i.v. fluid to use is yet to be established. Theoretical advantages of using hydroxyethyl starch (HES) for goal-directed therapy include a reduction in the total volume of fluid required, resulting in less tissue oedema. Recent work has demonstrated that new generations of HES have a good safety profile, but their routine use in the perioperative setting has not been demonstrated to confer outcome benefit. We randomly assigned 202 medium to high-risk patients undergoing elective colorectal surgery to receive either balanced 6% HES (130/0.4, Volulyte) or balanced crystalloid (Hartmann’s solution) as haemodynamic optimization fluid. The primary outcome measure was the incidence of gastrointestinal (GI) morbidity on postoperative day 5. Secondary outcome measures included the incidence of postoperative complications, hospital length of stay, and the effect of trial fluids on coagulation and inflammation. No difference was seen in the number of patients who suffered GI morbidity on postoperative day 5 [30% in the HES group vs 32% in the crystalloid group; adjusted odds ratio=0.96 (0.52–1.77)]. Subjects in the crystalloid group received more fluid [median (inter-quartile ranges) 3175 (2000–3700) vs 1875 (1500–3000) ml, P<0.001] and had a higher 24 h fluid balance [+4226 (3251–5779) vs +3610 (2443–4519) ml, P<0.001]. No difference in the incidence of postoperative complications was seen between the groups. Goal-directed fluid therapy is possible with either crystalloid or HES. There is no evidence of a benefit in using HES over crystalloid, despite its use resulting in a lower 24 h fluid balance. ISRCTN41882213 and EudraCT-2009-013872-29.